SIMULTANEOUS ADSORPTION AND ANTIBACTERIAL ACTIVITIES OF SURFACTANT-MODIFIED KAOLINITE (Jurnal Teknologi (Sciences & Engineering), 2020)
Water contamination problems caused by various contaminants (i.e. anionic and cationic compounds, and pathogenic bacteria) necessitate the advanced material development for simultaneous adsorption and antibacterial actions. In this study, kaolinite (Kao) was modified with surfactant hexadecyltrimethyl ammonium bromide (HDTMA-Br) (0.1, 1.0 and 4.0 mM) and they were characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and dispersion behaviour. No structural changes occurred after the adsorption of HDTMA-Br molecules on the Kao. In the simultaneous action study, the samples were tested for their adsorption capacity for cationic (methylene blue, MB) and anionic dyes (acid orange 7, AO7), and for antibacterial activities against Gram-negative (Escherichia coli ATCC11229) and Gram-positive bacteria (Staphylococcus aureus ATCC6538). HDTMA-modified Kao enhanced the adsorption of AO7 and the trend was correlated with the HDTMA adsorbed on Kao. The modified Kao with the highest HDTMA-Br concentration (KaoH4.0) showed 100% removal capacity for both dyes (AO7 and MB) and reduced the highest amount of both bacterial colonies. Therefore, the kaolinite modified with surfactant simultaneously enhanced the adsorption capacity of both positive and negative compounds, and increased the antibacterial activities against a wide spectrum of bacteria.